Influence of hydrogen on crystallization of cast magnesium alloys - E. I. Marukovich; V. Yu. Stetsenko; A. V. Stetsenko (Литьë и металлургия)
It is shown that hydrogen is a demodifying element of the structure of cast magnesium alloys during their crystallization. Hydrogen atoms, adsorbing on elementary nanocrystals in melts, prevent the combination of nanocrystals into the nucleus of crystallization of α‑phase microcrystals. As a result, molds with an unmodified structure are formed. Modifiers reduce the concentration of adsorbed hydrogen in the melts of magnesium alloys. This results in the milling of α‑phase microcrystals in castings as they solidify.